The Role of TikTok in Developing Gross Motor Skills in Children in Group B at Nur Azizah Kindergarten - Annisa Tuljannah Pabemba; Amrullah Amrullah; Fitriana Fitriana; Humaedi Humaedi (Journal of Educational Sciences, 2026)
Early Childhood Education (PAUD) plays a crucial role in developing all aspects of a child’s growth, including gross motor skills which involve large muscle groups for activities such as running, jumping, and kicking. The use of video-based social media, such as TikTok, has the potential to serve as a tool for stimulating children’s gross motor skills when used in a targeted manner and balanced with direct physical activity. This study aims to determine the role of TikTok use in the gross motor skills of children in Group B at Nur Azizah Kindergarten, as well as the roles of teachers and parents in supporting this process. The study employs a descriptive qualitative approach using observation, interviews, and documentation of the children during a three-week TikTok-based learning process. The observed aspects include the children’s agility, speed, and body coordination. The results indicate that regular use of TikTok enhances children’s interest, enthusiasm, and participation in physical activities. There was a significant improvement in children’s agility, speed, and coordination, with the percentage in the “Very Well Developed” category rising from 2.33% in the first week to 33.33% in the third week, while the “Not Yet Developed” category dropped to 0%. In conclusion, the social media platform TikTok serves as an effective learning tool that supports the gross motor development of young children, particularly in the areas of agility, speed, and body coordination, when used in a targeted and creative manner and accompanied by guidance from teachers or parents.